Lung abscess as a complication of pneumonia in 19-month old child - Bajić Dejana D.; Todorović Nemanja B.; Eić Nikola M.; Lalić-Popović Mladena N.; Milijašević Boris Ž. (Hospital Pharmacology, 2020)
Introduction: Community-acquired pneumonia is one of the most common diseases in infancy but most of these diseases have relatively simple course. We are presenting a case of child who developed lung abscess as a complication of pneumonia. Case Report: The goal of our case report is to point out that lung abscess is a relatively rare entity whose development is not always typical, sudden and acute, but also hidden, inconspicuous and perfidious. Although clinical picture and laboratory findings indicated that the pneumonia was cured, a single control CT scan showed that there was inflammation (hotspot) in the organism. Discussion: Lung abscess is a rare state which is developed as a complication only at 1% of pneumonias. Complications are rare and depend on the previous immunological status of the child and the presence of comorbidity. The duration of antibiotic therapy depends on the clinical and radiographic response of the patient. The chosen antibiotics have to cover a wide specter of Gram-positive and Gram-negative bacteria. Conclusions: The key role in making a diagnosis played radiological methods which were crucial in monitoring the evolution of the change itself, from its creation to regression. The triple antibiotic therapy with meropenem, vancomycin and metronidazole enabled an (excellent) recovery outcome.